2016
DOI: 10.1161/jaha.116.003954
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Life's Simple 7 and Noncardiovascular Disease: The Multi‐Ethnic Study of Atherosclerosis

Abstract: BackgroundThe American Heart Association introduced the Life's Simple 7 (LS7) metrics to assess and promote cardiovascular health. We examined the association between the LS7 metrics and noncardiovascular disease.Methods and ResultsWe studied 6506 men and women aged between 45 and 84 years, enrolled in the Multi‐Ethnic Study of Atherosclerosis. Median follow‐up time was 10.2 years. Each component of the LS7 metrics (smoking, body mass index, physical activity, diet, total cholesterol, blood pressure, and blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
91
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 107 publications
(100 citation statements)
references
References 37 publications
(78 reference statements)
6
91
1
2
Order By: Relevance
“…It comprises the following seven health and behavioral metrics: smoking status, physical activity, diet, body mass index (BMI), blood pressure, total cholesterol levels, and fasting blood glucose . Optimal CVH, defined by the LS7 score, has previously been associated with self‐reported health status and with a lower incidence of both CVD and non‐CVD outcomes, including lower mortality . Importantly, the LS7 framework represents a shift from focusing on disease (ie, CVD) to focusing on cardiovascular wellness (ie, CVH).…”
Section: Introductionmentioning
confidence: 99%
“…It comprises the following seven health and behavioral metrics: smoking status, physical activity, diet, body mass index (BMI), blood pressure, total cholesterol levels, and fasting blood glucose . Optimal CVH, defined by the LS7 score, has previously been associated with self‐reported health status and with a lower incidence of both CVD and non‐CVD outcomes, including lower mortality . Importantly, the LS7 framework represents a shift from focusing on disease (ie, CVD) to focusing on cardiovascular wellness (ie, CVH).…”
Section: Introductionmentioning
confidence: 99%
“…Points were summed, yielding a total CVH score ranging from 0 to 14 . As previously reported, CVH scores of 0 to 8, 9 to 10, and 11 to 14 were considered as inadequate, average, and optimal CVH, respectively …”
Section: Methodsmentioning
confidence: 99%
“…The AHA position statement recommends that individuals and populations meet specific criteria for 7 health metrics, collectively known as the AHA Life's Simple 7 (LS7), to be classified as having ideal CVH . Researchers have established an association between ideal CVH and a decrease in the risk for CVD, non‐CVD, and all‐cause mortality, in addition to lower healthcare costs, improvement in cognitive functioning, and higher quality of life…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The app has the potential to save millions of lives around the world, by being translated into the world's most spoken languages (covering over 90% of the world population), motivating and empowering people to reduce their risk of not only stroke but also other major NCDs that share common risk factors with stroke, such as ischaemic heart disease, dementia and diabetes mellitus. It was suggested that improving CVD health by improving control of CVD risk factors will also reduce the burden of cancer and other chronic disease 75. Such a motivational population-wide strategy could open a new page in primary prevention of not only stroke/CVD but also other NCDs worldwide.…”
Section: Where To From Here?mentioning
confidence: 99%